2021
DOI: 10.3390/rs13132501
|View full text |Cite
|
Sign up to set email alerts
|

An Efficient Multi-Sensor Remote Sensing Image Clustering in Urban Areas via Boosted Convolutional Autoencoder (BCAE)

Abstract: High-resolution urban image clustering has remained a challenging task. This is mainly because its performance strongly depends on the discrimination power of features. Recently, several studies focused on unsupervised learning methods by autoencoders to learn and extract more efficient features for clustering purposes. This paper proposes a Boosted Convolutional AutoEncoder (BCAE) method based on feature learning for efficient urban image clustering. The proposed method was applied to multi-sensor remote-sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Achieving an optimal model requires tuning many inter-dependent parameters [28]. In this work, the optimal parameters for the learning process, especially the number of filters of encoder output, learning rate, and batch size were obtained via the Keras Tuner optimizer developed by the Google team [87].…”
Section: Experimental Results From the Proposed Cae Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Achieving an optimal model requires tuning many inter-dependent parameters [28]. In this work, the optimal parameters for the learning process, especially the number of filters of encoder output, learning rate, and batch size were obtained via the Keras Tuner optimizer developed by the Google team [87].…”
Section: Experimental Results From the Proposed Cae Modelmentioning
confidence: 99%
“…Autoencoders (AEs) are one of the unsupervised architectures in deep neural networks and have been used in many applications in the field of RS. Therefore, some researchers have employed AEs to solve critical image processing challenges such as image classification [24][25][26], clustering [23,27,28], spectral unmixing [29] and image segmentation [30,31]. AEs have also been applied to deal with other important problems such as image fusion [32], change detection [33][34][35], pansharpening [36,37], anomaly detection [38,39], and image retrieval [40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the autoencoder is a data lossy compression algorithm. (3) Automatic learning means that the autoencoder automatically learns from data samples, making it easy to train a specific encoder to input a specified class without any new work (Rahimzad et al, 2021;Verma et al, 2021).…”
Section: Related Technologymentioning
confidence: 99%
“…Despite the paucity of relevant studies, researchers have demonstrated its effectiveness. Among them, the autoencoder is one of the unsupervised architectures embedded in DL models; it has been successfully used in the field of RS [52]. In the landslide detection task, Shahabi et al [53] first proposed an unsupervised model based on the convolutional auto−encoder (CAE), aiming to extract high−level features without using training data.…”
Section: Introductionmentioning
confidence: 99%